Rectal perforation, a rare presentation of a swollen limb - G. M., Sreenidhi; S., Jyothi; Satish, Vikyath (International Surgery Journal, 2021)
Soft tissue infection of right lower limb secondary to perforation of the gastrointestinal tract is very rare and the true incidence is probably higher, as some cases will be misdiagnosed as gas gangrene unless careful clinical examinations are performed. Only rapid recognition of the probable origin of the gas, coupled with aggressive, definitive therapy, can prevent the usually fatal course of this condition. In the absence of trauma or infection in a previously normal leg, subcutaneous emphysema of a limb should alert the clinician to the possibility of a gastrointestinal perforation as a source of the gas. Perforations of the gastrointestinal tract into the subcutaneous tissue can occur anywhere from the neck to the lower extremities. The mechanisms and anatomical pathways are discussed in this case report. Diversion colostomy with incision and drainage of the lower limb of the same is a safe and feasible option.